Management of follicular thyroid carcinoma should be individualised based on degree of capsular and vascular invasion - O’Neill, C.J.; Vaughan, L.; Learoyd, D.L.; Sidhu, S.B.; Delbridge, L.W.; Sywak, M.S. (European journal of surgical oncology, 2011)
Follicular thyroid carcinoma (FTC) includes a spectrum of neoplasms with varying propensity for metastasis. The aim of this study is to describe outcomes for FTC following multimodality treatment, with particular reference to the degree of capsular and vascular invasion and to recommend a rational management approach based on these characteristics. Patients with histologically confirmed FTC were identified from a prospectively maintained database. Details of intervention and long-term outcomes were obtained. Outcomes were compared between patients with minimally invasive follicular carcinoma (MI FTC) without vascular invasion (Group 1); angioinvasive MI FTC (Group 2); and those with widely invasive FTC (Group 3). Between May 1983 and December 2008, 124 patients with FTC were identified. The overall disease-free survival rate was 85% at a median of 40 months follow-up. Disease-free survival was 97%, 81% and 46%, respectively, in Groups 1, 2 and 3, and significantly different between groups ( p < 0.001). Thirteen patients in this series developed distant metastases including 2 in Group 1 and 6 in Group 2. Only patients <45 years of age with MI FTC and no vascular invasion had 100% disease-free survival. After multivariate linear regression, age ( p = 0.03) and the presence of vascular invasion ( p = 0.03) were the most powerful predictors of distant metastasis. Survival is improved in those with minimally invasive compared with widely invasive FTC. In patients <45 years with MI FTC without vascular invasion, hemithyroidectomy may be adequate treatment. All other patients with FTC should undergo total thyroidectomy and radioactive iodine ablation.